THE ROLE OF THE NATIONAL IDEA IN INCREASE OF HUMAN VALUES - Shodiyev , Jahangir Jurakulovich (Innovative Development in Educational Activities, 2023)
The article shows that the issue of human destiny and its value is reflected in our national idea, and it is analyzed that it has taken deep roots in the hearts of every person and the whole people living in this country, and has become a spiritual need and a requirement of life.